Efficiencies through the Automatic Control of Age-Profiled Manufacturing Machines: A Case Study of Cost-Saving in an Irish Production Facility. Issue 29 (2016) - Kent, Mary Doyle; Curtis, Helen; Darcy, Raymond; Stapleton, Larry; Norton, Stephen
Abstract: This paper asked if an effective energy measurement and monitoring system could be designed which was capable of controlling production machines to reduce operational costs. The solution had to be itself a low cost which could also be relatively easily deployed in developing regions. Developing regions are typically characterized by production facilities with outmoded equipment, but often have one or two more advanced machines available. This study identified a solution which evaluated energy consumption of machines at rest and oil consumption. It found that these two variables, when profiled against machine age, could be controlled in such a way as to significantly reduce production costs. Tests showed that, in addition to these variables, surge featured as an important variable which needed to be added to the control model. The solution itself could be deployed with very low cost. The experiment was carried out on CNC machines in a manufacturing site in Ireland.